(518) Special Conceptions of Socialist Economy: (Part 1) Conceptions of planning المفاهيم الخاصة بالاقتصاد الاشتراكي: (الجزء الأول) مفاهيم التخطيط - Sack, kurt; Linsel, Hermann (INP, 2024)
Special Conceptions of Socialist Economy: Planning.This content explores various concepts related to planning in the socialist economy, including: Conceptions concerning state authorities and leading principles. Conceptions concerning instruments of planning. Conceptions concerning national economic planning. Conceptions concerning the production process. Conceptions of industrial and enterprise planning: Categories of industrial and enterprise planning. Parts of industrial and enterprise plans. Conceptions concerning cost, credit, price, and return. Conceptions concerning manpower, labor productivity, and wages. Conceptions concerning investment and productive consumption.